Cultural Capital: Identity, Beliefs, and Local Wisdom in Ban Pho District, Chachoengsao Province - เรืองสุข, วรี; ทองแก้ว, สมศักดิ์; บุญทวี, อารียา (Journal of the Association of Researchers, 2024)
This research aimed to 1) explore and gather data on cultural capital in Ban Pho District, Chachoengsao Province; and 2) study the preservation of identity, beliefs, local wisdom, and value of cultural capital in Ban Pho District, Chachoengsao Province. The research areas included Thaphlub Subdistrict, Ban Pho Subdistrict Municipality, and Khlong Ban Pho Subdistrict. The qualitative research approach was utilized to investigate the identity, beliefs, local wisdom, and cultural values of Ban Pho District, Chachoengsao Province. The target groups for this research included cultural capital entrepreneurs, local scholars, local artists, the Ban Pho District Cultural Committee, civil society, and relevant government agencies to cultural capital, totaling 20 participants.The research findings indicated that the cultural capital of Ban Pho District, Chachoengsao Province, was divided into two main types, as follows: 1) Ten tangible cultural capital includes Prasat Sophon Temple, Inratsattharam Temple, Rong Si Lang Chinese Shrine, Rong Si Klang Chinese Shrine, Chao Pho Sa Che Suai and Chao Mae Thapthim Shrine, Sanam Chan Temple, Sanam Chan Local Arts and Culture Centre, Sanam Chan Market, Klong Ban Pho Temple, and Lat Nam Khem Temple. 2) Intangible cultural capital can be divided into three types. There are five rituals and festivals: the water route procession of the Sothorn Buddha Image, the fresh water receiving tradition, the Vegetarian Festival, the tradition of paying homage to Lord Hora, and the River Gratitude Day tradition. In terms of performing arts, there is one group: Huamai music (Naimai group). In terms of knowledge about nature and the universe, there are three topics: Khai Na Taek dessert, Melon planting (Baan Suan Melon), and traditional wisdom related to food and utensils from the way of life of communities along the river. The Ban Pho community has a distinct identity, beliefs, traditions, as well as lifestyle and local wisdom, with the Bang Pakong River serving as the central hub that connects the relationships of people in the community. This has led to the creation of cultural capital and cultural heritage, which has been passed down through generations.